BOUNDARY LAYER ANALYSIS FLOW PAST A POROUS ROTATING DISK WITH DUFOUR AND SORET EFFECTS - Yusuf, Abdulhakeem; Bima, Abdulrahman; Salihu, Nasiru Omeiza (FUDMA JOURNAL OF SCIENCES, 2022)
Analysis of a boundary layer flow past a porous rotating disk with Dufour and Soret effects are carried out mathematically with the formulated problem presented in its rectangular form. These problems correspond to the continuity, momentum, energy and concentration equations. The formulated equations (PDE) are contracted to a reduced nonlinear coupled equation (ODE) via some variables. The ODEs were solve using the decomposition method and the results obtained agreed with those in the literatures. The physical quantities that occur are presented and varied graphically on the fluid radial, tangential, axial velocity, temperature and concentration profiles. It seens that both ferro hydro dynamic (FHD) interactive parameter and rotational parameter enhances the radial, axial, temperature and concentration while they lead to decrease in tangential velocity of the fluid.